Historical Materialism, According to The Views of The Philosophers Marx And Engels, The Negro Revolution as An Example - Al-Shammari, Ashraq Ali Hussain; Hussein Al-Shammari, Abbas Ali (International Journal of Psychosocial Rehabilitation, 2020)
The research was divided into research into an introduction, two studies, and a conclusion. We discussed in the first topic about the most prominent opinions that materialistic philosophers brought about, how these opinions were added in history, as well as about the rise of the Negro revolution and its most prominent founders, and how it managed to attract people to it. As for the second topic, it was about the establishment of the revolution, how it managed to bring people together for it, declaring the establishment and direct confrontation, and what measures were taken by the Abbasid state in order to be able to eliminate it. In conclusion, we announced the most prominent results that we reached in this research.